Effects of flow intermittency and pharmaceutical exposure on the structure and metabolism of stream biofilms - Corcoll, Natàlia; Casellas, Maria; Huerta, Belinda; Guasch, Helena; Acuña, Vicenç; Rodríguez-Mozaz, Sara; Serra-Compte, Albert; Barceló, Damià; Sabater, Sergi (Science of The Total Environment, 2015)
Increasing concentrations of pharmaceutical compounds occur in many rivers, but their environmental risk remains poorly studied in stream biofilms. Flow intermittency shapes the structure and functions of ecosystems, and may enhance their sensitivity to toxicants. This study evaluates the effects of a long-term exposure of biofilm communities to a mixture of pharmaceutical compounds at environmental concentrations on biofilm bioaccumulation capacity, the structure and metabolic processes of algae and bacteria communities, and how their potential effects were enhanced or not by the occurrence of flow intermittency. To assess the interaction between those two stressors, an experiment with artificial streams was performed. Stream biofilms were exposed to a mixture of pharmaceuticals, as well as to a short period of flow intermittency. Results indicate that biofilms were negatively affected by pharmaceuticals. The algal biomass and taxa richness decreased and unicellular green algae relatively increased. The structure of the bacterial (based on denaturing gradient gel electrophoresis of amplified 16S rRNA genes) changed and showed a reduction of the operational taxonomic units (OTUs) richness. Exposed biofilms showed higher rates of metabolic processes, such as primary production and community respiration, attributed to pharmaceuticals stimulated an increase of green algae and heterotrophs, respectively. Flow intermittency modulated the effects of chemicals on natural communities. The algal community became more sensitive to short-term exposure of pharmaceuticals (lower EC50 value) when exposed to water intermittency, indicating cumulative effects between the two assessed stressors. In contrast to algae, the bacterial community became less sensitive to short-term exposure of pharmaceuticals (higher EC50) when exposed to water intermittency, indicating co-tolerance phenomena. According to the observed effects, the environmental risk of pharmaceuticals in nature is high, but different depending on the flow regime, as well as the target organisms (autotrophs vs heterotrophs).
Keywords: Algae; Bacteria; Ecotoxicology; Intermittent rivers; Multiple stressors; Pollution; dept.che